Electrochemistry of flavins - Tan, Serena Li Jun (2015)
The electrochemical behavior of riboflavin, FMN, FAD and 2 synthesized flavins were examined in aqueous (buffered and non-buffered) and non-aqueous media (with varying amounts of water and free protons), using voltammetry, electrolysis, UV-vis and EPR spectroscopy, and were found to display a range of electron-transfer mechanisms from the most hydrophobic environments to environments with the most number of free protons. In aprotic organic solvents, the N3-protonated riboflavin (and flavin 1) are reduced by one-electron to form the anionic radical, which undergo a homogeneous proton transfer reaction with another oxidized flavin (starting material) to produce the neutral radical and deprotonated flavin, which are both able to undergo further reduction at the electrode surface, forming FlH– and Fl2•– respectively. At faster scan rates the proton transfer reaction is outrun, and the anionic radical is further reduced to the dianion. Digital simulation techniques enabled the determination of four formal electrode potentials as well as the equilibrium and rate constants associated with four homogeneous reactions. For the N3-methylated flavin 2, the radical anion does not undergo a proton transfer reaction in aprotic organic solvents due to the lack of a suitable proton source, and is reduced to the dianion, resembling N3-protonated flavins at high scan rates. The dianion, however, is able to deprotonate the trace water present in the solvent, forming FlH–. Addition of excess water to these solutions showed that the anionic radical also undergoes proton transfer reactions with water at very high water concentrations. For unbuffered aqueous solutions of FMN and FAD at intermediate to high pH, the hydrogen-bonded dianion is formed in one voltammetric wave, which can then deprotonate water to form FlH–, while at sufficiently low pH ([H+] ≥ [Fl]), a 2e–/2H+ reduction occurs in one voltammetric wave. In buffered aqueous solutions at pH 3 – 5, a direct a 2e–/2H+ reduction to FlH2 was observed, while at pH 7 – 11, a 2e–/H+ reduction to FlH– was observed. At sufficiently high scan rates, another oxidative wave was observed corresponding to the oxidation of the hydrogen-bonded dianion, indicating that an equilibrium process is occurring after reduction.